Transfusion‐transmitted malaria masquerading as sickle cell crisis with multisystem organ failure. Issue 6 (9th March 2018) - Maier, Cheryl L.; Gross, Phillip J.; Dean, Christina L.; Chonat, Satheesh; Ip, Andrew; McLemore, Morgan; El Rassi, Fuad; Stowell, Sean R.; Josephson, Cassandra D.; Fasano, Ross M.
Abstract : BACKGROUND: Fever accompanying vaso‐occlusive crisis is a common presentation in patients with sickle cell disease (SCD) and carries a broad differential diagnosis. Here, we report a case of transfusion‐transmitted malaria in a patient with SCD presenting with acute vaso‐occlusive crisis and rapidly decompensating to multisystem organ failure (MSOF). CASE REPORT: An 18‐year‐old African American male with SCD was admitted after multiple days of fever and severe generalized body pain. He received monthly blood transfusions as stroke prophylaxis. A source of infection was not readily identified, but treatment was initiated with continuous intravenous fluids and empiric antibiotics. The patient developed acute renal failure, acute hypoxic respiratory failure, and shock. He underwent red blood cell (RBC) exchange transfusion followed by therapeutic plasma exchange and continuous veno‐venous hemodialysis. A manual peripheral blood smear revealed intraerythrocytic inclusions suggestive of Plasmodium, and molecular studies confirmed Plasmodium falciparum infection. Intravenous artesunate was given daily for 1 week. A look‐back investigation involving two hospitals, multiple blood suppliers, and state and federal public health departments identified the source of malaria as a unit of RBCs transfused 2 weeks prior to admission. CONCLUSIONS: Clinical suspicion for transfusion‐related adverse events, including hemolytic transfusion reactions and transfusion‐transmitted infections, should be high in typically and atypically immunocompromised patient populations (like SCD), especially those on chronic transfusion protocols. Manual blood smear review aids in the evaluation of patients with SCD presenting with severe vaso‐occlusive crisis and MSOF and can alert clinicians to the need for initiating aggressive therapy like RBC exchange and artesunate therapy.